Embedding International Entrepreneurship into Postgraduate Business Programmes - Bell, Jim; Loane, Sharon; Hegarty, Cecilia; Morrow, Trevor (Senate Hall, 2010)
Despite growing policy and research interest in entrepreneurship relatively little attention has been focused on the personal and professional development of international entrepreneurs. This issue needs to be addressed in light of the globalisation of the international business environment and the emergence of entrepreneurial "born global" firms that internationalise rapidly. It is of particular importance to small open economies that are highly dependent on such firms for export-led growth and economic development. This contribution outlines and evaluates a number of approaches that have been developed to embed international entrepreneurship into postgraduate business programmes at the authors' institution. Their design is based upon a three-stage model for international business education proposed by Arpan et al (1993), wherein cross-cultural immersion is a crucial pedagogic component. Following a description and evaluation of these approaches, we posit that they offer useful perspectives for educational initiatives in other locations seeking to develop a greater focus on international entrepreneurship Keywords: international, entrepreneurship, education
Keywords: international|entrepreneurship|education